Population Dynamics of Whitefly, Bemisia tabaci and Incidence of Mungbean Yellow Mosaic India Virus (MYMIV) on Blackgram - Marabi, R. S.; Chaukikar, K.; Das, S. B.; Bhowmick, A. K. (International Journal of Bio-resource and Stress Management, 2017)
An investigation was conducted on population dynamics of whitefly, Bemisia tabaci and incidence of mungbean yellow mosaic India virus (MYMIV) on blackgram during Kharif 2015–16. observations of adult whitefly was recorded at weekly interval through yellow sticky trap at the field by installing just above the crop canopy for 24 hours and percent disease incidence of MYMIV was recorded. Results revealed that the whitefly was first observed from 28th SMW (15.83 whiteflies sticky trap-1). During this period maximum and minimum temperature was 30.40C and 24.20C while morning and evening RH were 91% and 74%, respectively. Further, wind speed, sunshine, rainfall and rainy days were observed 7.3 (kmh-1), 6.8 (hrs), 203.2 (mm) and 6 (days), respectively. The whitefly population was reached at its peak (67.83 whiteflies sticky trap-1) at 36th SMW. Correlation studies with maximum temperature was exhibited significantly positive (r=0.659), whereas wind speed (r=-0.812) and rainfall (r=-0.809) were showed highly negative significant association with whitefly. Path analysis revealed that evening RH had highest direct positive effect (1.4106) on whitefly followed by maximum temperature (1.0663), sunshine (0.0675), rainfall (0.0501) whereas, direct negative effect was exerted via rainy days (-0.6289) followed by wind speed. The first incidence of MYMIV (2.35%) was recorded on blackgram at 30th SMW which was gradually increased and reached at peak (100.00%) on 36th SMW. Maximum temperature showed significantly positive correlation (r=0.630) with incidence of MYMIV. Results revealed that severe attack of whitefly was occurred as pest outbreak and MYMIV incidence as epidemic form on blackgram due to erratic abiotic factors.